Altered pattern of connexin40 distribution in persistent atrial fibrillation in the goat. - Van Der Velden HM; Van Kempen MJ; Wijffels MC; Van Zijverden M; Antoinette Groenewegen W; Allessie MA; Jongsma HJ (Journal of Cardiovascular Electrophysiology, 1998)
Introduction: Since altered expression of gap junction proteins (connexins) in diseased myocardial tissue may lead to abnormal electrical coupling between cardiomyocytes and hence contribute to arrhythmogenesis, the expression of connexin(Cx)40 and Cx43 was studied in atrial appendage from goats in sinus rhythm (SR) and persistent atrial fibrillation (AF). Methods and Results: Biopsies were taken from the left and right atrial appendages from goats in SR or after pacing-induced persistent AF. Analyses of Cx40 and Cx43 mRNA and protein levels, using quantitative (competitive) polymerase chain reaction and western blotting, respectively, revealed no significant changes in the overall expression of Cx40 and Cx43 as a result of persistent AF. At the cellular level, immunohistochemistry and confocal laser scanning microscopy showed a homogeneous distribution of either connexin in atrial sections taken during SR. After induction of AF, the distribution of Cx43 gap junctions was unchanged whereas the Cx40 pattern showed marked inhomogeneities with small areas (0.15 to 0.6 mm in diameter, 25% of section surface area) of low-density Cx40 located between larger areas of normal (unchanged) Cx40 density. Activation mapping (244 electrodes, spatial resolution 2.25 mm) of the right atrial wall did not reveal changes in atrial conduction velocity. Conclusion: Pacing-induced persistent AF in the goat gave rise to changes in the spatial organization of Cx40 gap junctions. Although the overall conduction velocity appeared not to have changed, microheterogeneities in conduction due to the local redistribution of Cx40 gap junctions might have contributed to the initiation and maintenance of AF.